Measuring the divergent thinking ability in biology science process skills of elementary school students based on tutoring activities - Ikhsanudin Ikhsanudin; Bambang Subali (IAIN Palangka Raya, 2023)
Learning in the current era is often directed at developing creativity. Increasing creativity is very close to divergent thinking skills. This study aims at measuring the divergent thinking ability in biology science process skills of the sixth-grade students at elementary schools in one regency in relation to the tutoring activities along with the effect of gender and parent’s occupations. This study is a descriptive quantitative study employing a survey method. The sample includes 603 sixth grade students at 18 elementary schools in one regency which was determined using a purposive sampling technique. The divergent thinking ability is indicated by the scores of the open-ended test. The tutoring programs, gender, and parent’s professions of the samples were obtained from questionnaires. Scoring guidelines and descriptive statistics were used for data analysis. The mean of testee joining the tutoring program is relatively low (mean=17.93/40.00, SD=6.02). This empirically shows that the development of divergent thinking ability in biology science process skills at elementary school is not optimal yet, particularly in the research samples. There is a relationship between the gender and parent’s occupations with the student’s divergent thinking ability of biology science process skills regarding the tutoring activities. This can be studied and examined further.